The fasces a history of Ancient Rome's most dangerous political symbol - Brennan, T. Corey 1959- (Oxford scholarship online, 2023)
In ancient Rome, the fasces were a bundle of wooden rods bound with a leather cord, in which an axe was placed-in essence, a mobile kit for corporal or capital punishment. This book is the first attempt to explain in detail precisely how the ancient Romans made a familiar and highly effective spectacle of the fasces, and then how later generations understood, used, and abused this symbol